Corn storage and marketing feasibility in northern Mississippi - Milstead, Andrew (Kansas State University, 2017)
On-farm grain storage plays a key role in the production and distribution of corn in the United States. It can have economic impacts on a farm’s profitability and production efficiency over time. With the free market system of the United States, market fundamentals are a key component of decisions made on the farm regarding construction of grain storage facilities and how they are used in marketing decisions throughout a given production and marketing year. This analysis researches how grain storage decisions in the Northern Mississippi area are effected by corn basis differentials between the Memphis, TN river market and the Northern Alabama corn market. Corn basis differentials are considered along with annual changes in corn futures market carry in response to variations in grain market fundamentals. The profitability of constructing, maintaining, and operating on-farm grain storage is analyzed based on the local history of the local corn market basis patterns and the carry priced into the corn futures market. Through this analysis it was found that the biggest obstacle affecting the profitability of on-farm grain storage was the upfront cost of the facility. As costs of the facility were incurred, grain had to be stored for longer periods of time in order to be profitable based on history of improved basis and market carry over time. On-farm storage became profitable over a shorter storage period once the upfront costs of grain storage and handling facilities were paid based on the operating costs and market conditions within the analysis. On-farm storage can be a useful tool for a farm to increase profitability over time, beyond the scope of this analysis. This analysis proves that in the Northern Mississippi area over time, grain storage can be profitable based on improved cash basis and futures market carry. However, due to ever-changing market conditions, on-farm grain storage does not replace the need for the development of grain marketing plans in order to increase the likelihood of profitability.
Keywords: Grain Storage; Grain Basis; Market Carry; Corn Market; Depreciation; Northern Mississippi